Comparing Experts and Novices on Scaffolded Data Visualizations using Eye-tracking - Kathryn Stofer; Xuan Che (Bern Open Publishing, 2014)
Spatially-based scientific data visualizations are becoming widely available, yet they are often not optimized for novice audiences. This study follows after an investigation of ex-pert and novice meaning-making from scaffolded data visualizations using clinical inter-views. Using eye-tracking and concurrent interviewing, we examined quantitative fixation and AOI data and qualitative scan path data for two expertise groups (N = 20) on five versions of scaffolded global ocean data visualizations. We found influences of expertise, scaffolding, and trial. In accordance with our clinical interview findings, experts use dif-ferent meaning-making strategies from novices, but novice performance improves with scaffolding and guided practice, providing triangulation. Eye-tracking data also provide insight on meaning-making and effectiveness of scaffolding that clinical interviews alone did not.